MODERN MARKETING TECHNOLOGIES IN THE ADVERTISING BUSINESS - M. Orlova; A. Serzhantov; A. Cherskikh (Вестник университета)
The article shows the need for new approaches to the creation of competitive advantage for the Russian companies working in the field of advertising. Integrated use of marketing interaction marketing technology and marketing experience will allow Russian companies to maximize customer value and achieve a competitive edge in a turbulent market environment.